MULTI INPUTS MULTI OUTPUTS (MIMO) DC DC CONVERTER FOR DC MICRO GRID APPLICATIONS - Ahmad Faudzi, Muhammad Izwan Asraf (2017)
Microgrid are seen to be the future of electric power industry. This is because of over dependency on fossil fuel source which is non-renewable resources that will decrease day by day. In order to minimize grid expansion, DC microgrid is the suitable alternative ways. This is because to expand the grid, area needed is very large and cost is very high. A DC-DC converter is a type of electronic converter that is used in DC microgrid applications to convert one level of voltage to another for use in DC microgrid system.